MOBILISASI PROGRESIF LEVEL 1 PADA PENINGKATAN HEMODINAMIK PASIEN ST ELEVASI MIOKARD INFARK (STEMI): CASE STUDY - Yuliana; Ahmat Pujianto; Hendy Lesmana; Maria Imaculata Ose; M. Akbar Nugraha (Universitas Kadiri, 2025)
Heart disease Acute Coronary Syndrome (ACS) causes a death every minute in the world. The impact of ACS itself includes pain due to myocardial ischemia, activity intolerance due to an imbalance between oxygen supply and demand due to blockage of the coronary artery walls, both of which can affect the patient's hemodynamic status to become unstable. For patients whose hemodynamic status is unbalanced, the recommended solution is to train the patient to tolerate changes in position rather than leaving the patient in a supine position. Progressive Mobilization is a form of exercise to overcome the problem of post-immobilization activity tolerance in ACS patients, which is useful for preventing and minimizing anxiety and depression, preventing thromboembolism, reducing morbidity, and improving cardiovascular function which can cause hemodynamic instability and reducing recurrence rates in ACS patients. This writing aims to analyze level 1 progressive mobilization training interventions using the case study method of a nursing care approach. The sample in this writing consisted of 2 patients and was carried out when they were pain-free and given the same treatment twice a day for 2 days, the sampling technique used purposive sampling, data analysis with 3 stages, namely: descriptive analysis, Pattern Matching, and quantitative analysis. The results of implementing Level 1 Progressive Mobilization in this writing show an increase in hemodynamic status (BP, HR, RR, TB, & SPO2) pre and post Level 1 Progressive Mobilization but still within normal limits.